Perubahan Orientasi Keberfungsian Lahan dan Nilai Sosial Petani Pasca Gempa dan Likuifaksi di Sulawesi Tengah - Siti Yuliaty Chansa Arfah; Hardiyanti Sultan; Ihdiani Abubakar (Balai Pelatihan Pertanian Jambi, 2021)
The method used in this research is descriptive qualitative research method using the case study method. Qualitative descriptive research aims to describe, summarize various conditions and phenomena of social reality that exist in society which are the object of research and draw these social realities to the surface. Data analysis includes descriptive analysis and economic analysis related to changes in recommended commodities according to land conditions after conversion of agricultural land functions and associated social values ​​analyzed. The results showed that 65 percent of farmers lost their agricultural land as a whole and the remaining 35 percent still owned their land intact. Farmers who lost their land changed jobs to become agricultural laborers, construction workers, breeders, traders and others who did not even work as much as 10 percent. Farmers who still cultivate agricultural crops choose to plant horticultural crops, namely eggplant, chilies, kale, string beans and green beans. Total revenue of farmers after the earthquake and liquefaction decreased by 35.46 percent. However, from the income side, there was an increase in post-earthquake income by 0.97 percent. The values ​​that change after a disaster are the value of rationality, economic value, the value of solidarity or mutual assistance and the value of education.